2005
DOI: 10.1021/ac050534o
|View full text |Cite
|
Sign up to set email alerts
|

Distinction of Leu and Ile Using a Ruthenium(II) Complex by MALDI-LIFT-TOF/TOF-MS Analysis

Abstract: The novel N-terminal labeling method using a ruthenium(II) complex derivative characteristically indicated a(n) and d(n) (N-terminal) fragment ions in high sensitivity by MS/MS analysis (MALDI-LIFT or ESI-CID). Although these fragment ions depended on a fragmentation process by MS/MS analytical methods to some degree, each case indicated similar side-chain cleavage patterns. The labeling method allows accurate distinction of amino acid residues by MS/MS analysis even if the residues are structural isomers such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…This finding is most likely attributable to the presence of the stable terminal C=O + group. In our study, the dicationic <Ru> moiety easily enhanced the a n or the d n series with the deprotonated neutral NCHR or the NHCHCH 2 group at the terminus 24. From a 0 (<Ru>), amino acid sequencing can be read successively to reach the C‐terminus.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…This finding is most likely attributable to the presence of the stable terminal C=O + group. In our study, the dicationic <Ru> moiety easily enhanced the a n or the d n series with the deprotonated neutral NCHR or the NHCHCH 2 group at the terminus 24. From a 0 (<Ru>), amino acid sequencing can be read successively to reach the C‐terminus.…”
Section: Resultsmentioning
confidence: 94%
“…The detection limits are less than low fmol levels, which are sufficient for analyzing each spot in two‐dimensional electrophoretic separation 21. Furthermore, the <Ru>‐CO‐labeling method enables distinctions between structural isomers (e.g., leucine and isoleucine) according to their side‐chain cleavage 24. In our previous paper, we found that the reagent reacted with both the N‐terminal and the lysine ε ‐amino groups of the protein; thus, the N‐terminal labeled peak should be selected among several <Ru>‐CO‐labeled peaks 21.…”
mentioning
confidence: 99%
“…[12][13][14][15] According to this sequencing method, the amino groups of the protein are selectively labeled with an active ester of bis(terpyridine)ruthenium (II) (hRui-CO-labeling reagent, Fig. 1).…”
mentioning
confidence: 99%
“…Recently, O'Hair and coworkers demonstrated the formation of cationic peptide radicals with trivalent chromium, manganese, iron, and cobalt salen complexes [32]. While the previous examples demonstrate the use of organometallic complexes in which the amino acid or peptide interact with the metal as ligands, covalent derivatization of the N-terminal with a ruthenium(II) complex has also been reported [33,34]. This elegant approach proved successful in generating radicals [a Ru(I) complex is generated upon ionization], the radical cation is formed during the ionization either by MALDI or by ESI.…”
mentioning
confidence: 99%